The TRUST Principles as an assessment tool for data repositories - Silva, Lucas Henrique Alves da (2021)
Scientific data repositories act as important tools to support data storage, preservation and sharing. In this sense, the TRUST Principles emerge as a set of guidelines that seek to guarantee the reliability of digital data repositories. This research aims to verify the applicability of TRUST Principles as an assessment tool for data repositories, based on the analysis of the “Covid-19 Data Sharing / BR” repository. For this, two instruments were used: first, a set of criteria was developed to assess the repository's adherence to each of the TRUST Principles; second, a scoring system capable of assessing the repository's adherence to each criterion, on a scale graded from one to five, was formulated, the average score obtained in each principle was named trustworthiness degree. The scoring system was modeled using a software developed in the PHP programming language. It was observed that the principle with the highest value in the repository was Responsibility, while a low adherence to the Technology principle was noted. The research found that the TRUST Principles can be used as a useful certification tool for data repositories, as they direct their focus to very specific aspects of the repositories.